(untitled) (Mustansiria Dental Journal, 2005)
Abstract: All previous studies concerning the soft tissue changes associated with upper jaw osteotomy related to the use of the most common approaches to the anterior maxilla i.e. Wassmund, Wunderer and Cuper approach. Few of these directed to assess the upper lip cross sectional area as a factor in prediction pmpose. A new approach by mean of 3-sided mucoperiostcal flap adopted in this study to expose the premaxilla. From the clinical observation, there is slight lengthening ofthe upper lip after surgery. This study conducted to assess the upper lip cross sectional area after maxillary segmental setting up osteotomy using this approach(for prediction purpose), and assess the validity of the use of the 3-sided mucoperiosteal flap. Presurgical and post surgical cephalometric radiographs of (9) patients were compared by superimposition of acetate tracings on special references. Cross sectional lip area then calculated presurgically and at two intervals following surgical intervention (immediately after surgery i.e. with in 2 days and the longest possible post surgical follow up) using simpson role. Analysis of data showed that the cross sectional lip area significantly increased by a mean of 38% ranged (23% - 58%) immediately after surgery. While at about 3 months interval, it became about 17% ranged (2% — 34%) the study showed also an acceptable accessibility with the use of this 3-sided flap.